2003
DOI: 10.1103/physreve.67.031702
|View full text |Cite
|
Sign up to set email alerts
|

Bent-core liquid crystals forming two- and three-dimensional modulated structures

Abstract: Two columnar phases of bent-core molecules have been observed, with a two-dimensional (2D) structure modulated in the plane perpendicular to the direction of the spontaneous polarization vector. The phases are switchable under an applied electric field, contrary to the commonly observed 2D modulated B1 phase. These new phases are built from broken smectic layers with orthogonal or tilted molecules. The evidence for a 3D structure in which the density modulations along and perpendicular to the spontaneous polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
94
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 14 publications
7
94
1
Order By: Relevance
“…In ref. [7], this behaviour was concluded from the electro-optical response in a switchable B 1 phase. As shown in ref.…”
mentioning
confidence: 87%
“…In ref. [7], this behaviour was concluded from the electro-optical response in a switchable B 1 phase. As shown in ref.…”
mentioning
confidence: 87%
“…10), and above 25 V/μm the polarization of B 1 phase saturates but its value is smaller than 120 nC/cm 2 . This effect is most probably due to short range ferroelectric order and/or modulated structures (Szydłowska, 2003). …”
Section: Electro-optic Methodsmentioning
confidence: 99%
“…A general symbol of B 2 phase can be written as follows: SmC SA P FA , where index "S" stands for synclinic, A -for anticlinic order of molecules in two neighboring layers, F -for ferroelectric and A -antiferroelectric order of polarization vectors. Banana-shaped compounds may form both lamellar and/or columnar mesophases (Szydłowska, 2003) that have become a subject of intensive experimental (Reddy & Tschierske, 2006) and theoretical studies (Vaupotič, 2006) in the last decades. In the first place research on electro-optic switching in ferro-and anti-ferroelectric phases composed of bent-core molecules has been done because of possible practical applications (Walba el al., 2000;Reddy & Tschierske, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that the polar switching in "banana phases" can also take place by another mechanism, which is based on the collective rotation of the molecules around their long axes (Figure 2 a). In polar smectic A (SmAP) phases [4,5] and in B 1rev phases formed by SmAP-like layer fragments [6] this mechanism is the only possibility for polar switching. There are a few examples that this switching mechanism can also occur in tilted SmCP A phases [7][8][9] as well as in B 1rev phases with SmCP-like layer fragments, [6] mostly under special experimental conditions.…”
mentioning
confidence: 99%
“…In polar smectic A (SmAP) phases [4,5] and in B 1rev phases formed by SmAP-like layer fragments [6] this mechanism is the only possibility for polar switching. There are a few examples that this switching mechanism can also occur in tilted SmCP A phases [7][8][9] as well as in B 1rev phases with SmCP-like layer fragments, [6] mostly under special experimental conditions. Nakata et al [8] and Bedel et al [9] were able to detect this switching mechanism above a critical electric field.…”
mentioning
confidence: 99%